2000
DOI: 10.1099/00207713-50-4-1641
|View full text |Cite
|
Sign up to set email alerts
|

Polyphasic assignment of an aromatic-degrading Pseudomonas sp., strain DJ77, in the genus Sphingomonas as Sphingomonas chungbukensis sp. nov.

Abstract: Pseudomonas sp. strain DJ77, which was described as an aromatic-degrading bacterium, was investigated to clarify its taxonomic position. Phylogenetic analysis based on 16S rDNA sequences indicated that the strain belonged to the genus Sphingomonas and formed a monophyletic clade with the type strains of Sphingomonas chlorophenolica, Sphingomonas herbicidovorans and Sphingomonas yanoikuyae with sequence similarity values of 981, 961 and 956 %, respectively. Genomic relatedness based on DNA-DNA hybridization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
53
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 28 publications
0
53
0
1
Order By: Relevance
“…The DNA G+C content of strain KOPRI 13649 T , as determined using the thermal denaturation method of Kim et al (2000), was 29?8 mol%, a value similar to that of P. burtonensis. The major respiratory quinone was determined to be menaquinone according to the reversed-phase TLC method described by Kim et al (2000) and was confirmed to be MK-6 following the HPLC method of Collins (1985).…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…The DNA G+C content of strain KOPRI 13649 T , as determined using the thermal denaturation method of Kim et al (2000), was 29?8 mol%, a value similar to that of P. burtonensis. The major respiratory quinone was determined to be menaquinone according to the reversed-phase TLC method described by Kim et al (2000) and was confirmed to be MK-6 following the HPLC method of Collins (1985).…”
mentioning
confidence: 86%
“…The major respiratory quinone was determined to be menaquinone according to the reversed-phase TLC method described by Kim et al (2000) and was confirmed to be MK-6 following the HPLC method of Collins (1985).…”
mentioning
confidence: 99%
“…nov. IMMIB HF-1 T ; 2, S. amiense YT T ; 3, S. cloacae JCM 10874 T ; 4, S. yanoikuyae JCM 7371 T ; 5, S. chlorophenolicum DSM 8671; 6, S. herbicidovorans DSM 11019 T ; 7, S. chungbukense KCTC 2955 T ; 8, S. indicum B90A T ; 9, S. japonicum UT26 T ; 10, S. francense Sp+ T ; 11, S. xenophagum BN6 T ; 12, S. aromaticiconvertens DSM 12677 T . Data are from the following sources: strain 1, this study; strains 2-6, Ushiba et al (2003); strain 7, Kim et al (2000); strains 8-10, Pal et al (2005); strain 11, Stolz et al (2000) and strain 12, Wittich et al (2007). +, Positive; 2, negative; ND, no data available.…”
Section: Description Of Sphingobium Olei Sp Novmentioning
confidence: 99%
“…Table 1. Cellular fatty acid composition of strain RW16 T , Sphingobium species and Sphingomonas cloacae Strains: 1, Sphingobium amiense JCM 11777 T (data from Ushiba et al, 2003); 2, Sphingobium chlorophenolicum ATCC 33790 T (data from this study); 3, Sphingobium chungbukense DJ77 T (Kim et al, 2000); 4, Sphingomonas cloacae JCM 10874 T (Fujii et al, 2001); 5, Sphingobium francense CCM 7288 T (Pal et al, 2005); 6, Sphingobium herbicidovorans DSM 11019 T (this study); 7, Sphingobium indicum CCM 7286 T (Pal et al, 2005); 8, Sphingobium japonicum CCM 7287 T (Pal et al, 2005); 9, strain RW16 T ; 10, Sphingobium xenophagum DSM 6383 T ; 11, Sphingobium yanoikuyae IFO 15102 T (data in columns 9-11 from this study). Values shown are percentages of total fatty acids.…”
mentioning
confidence: 99%